Серая шейка - Мамин-Сибиряк Дмитрий Наркисович (Книги - мои друзья, 2018)
Экземпляры: (20191002) / Инвентарный номер: 40943 / Цена: 98.70 / Сис.шифр: Р2 / Авт.знак: М 22 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6